Optimal Design of MVDC Power Cables for Different Air Pressures for Wide-Body All-Electric Aircraft - Farzana Islam; Mona Ghassemi (IEEE Access)
The transportation sector is responsible for approximately one-third of all United States greenhouse gas (GHG) emissions. To address this issue and mitigate the effects of global warming, electrification of the transportation sector, including the aviation sector, is essential. Although efforts have been made to advance manned narrow-body aircraft to get a substantial reduction in greenhouse gas emissions, wide-body aircraft must become a reality. This means the introduction of high-density, high-power electric power systems (EPS) in all-electric aircraft. In this article, we studied the electric power system of NASA N3-X, which was redesigned to make it an all-electric aircraft, and designed an optimal cable system for that. Cable design for aircraft’s medium voltage direct current systems faces thermal challenges due to low pressure during cruising time. To design a low-mass EPS and its cable system, this study is crucial to optimize cable configuration. In this study, we have explored different loading conditions that an aircraft faces during take-off and cruising altitude under normal conditions and all single contingency situations. The comparative study of electrical and thermal performance of bipolar MVDC power cable operating in 18.8 kPa at cruising height and during take-off at atmospheric pressure is for the first time studied in this article.